Financing Public Goods and Attitudes Toward Immigration - Romero, J (Elsevier B.V., 2016)
We study a model where individuals choose both the level of provision of a public good and the quota of low-skilled immigrants that are allowed into the country. Individuals can supplement the public good in the private market. Immigrants affect natives through three channels: (i) the labor market; (ii) tax collection; (iii) the quality of the public good. We find that the higher the political weight of the rich (highly skilled) is, the less tolerant the poor and the middle-class are toward immigration and the more demanding they are toward increasing public spending. The rich are the most favorable to immigration. As they have more weight, the political outcome is closer to their preferences and further from the preferences of the other groups. We use data from the European Social Survey to test the implications of our model. © 2016 Elsevier B.V.